Hypoglycaemia and accident risk in people with type 2 diabetes mellitus treated with non‐insulin antidiabetes drugs. Issue 4 (22nd November 2012) - Signorovitch, J. E.; Macaulay, D.; Diener, M.; Yan, Y.; Wu, E. Q.; Gruenberger, J.‐B.; Frier, B. M.
<x xml:space="preserve">Abstract</x> Aims To assess associations between hypoglycaemia and risk of accidents resulting in hospital visits among people with type 2 diabetes receiving antidiabetes drugs without insulin. Methods People with type 2 diabetes who were not treated with insulin were identified from a US‐based employer claims database (1998–2010). Following initiation of an antidiabetes drug, the occurrence of accidents resulting in hospital visits was compared between people with, and without, claims for hypoglycaemia using multivariable Cox proportional hazard models adjusted for demographics, comorbidities, prior treatments and prior medical service use. Additional analyses were stratified by age 65 years or older. Results A total of N = 5582 people with claims for hypoglycaemia and N = 27 910 with no such claims were included. Accidents resulting in hospital visits occurred in 5.5 and 2.8% of people with, and without, hypoglycaemia, respectively. After adjusting for baseline characteristics, hypoglycaemia was associated with significantly increased hazards for any accident [hazard ratio (HR) 1.39, 95% CI 1.21–1.59, p < 0.001], accidental falls (HR 1.36, 95% CI 1.13–1.65, p < 0.001) and motor vehicle accidents (HR 1.82, 95% CI 1.18–2.80, p = 0.007). In age‐stratified analyses, hypoglycaemia was associated with greater hazards of driving‐related accidents in people younger than age 65 and falls in people aged 65 or older. Conclusions In people with type 2 diabetes receiving antidiabetes drugs without insulin, hypoglycaemia was associated with a significantly higher risk of accidents resulting in hospital visits, including accidents related to driving and falls.